(untitled) (Global Journal of Human-Social Science, 2019)
Religion-related stigma and discrimination towards transgender are common phenomena in the current world Despite the legal recognition of hijra those people were denied basic civil and human rights such as marriage or inherent property rights Like many colonized countries Bangladesh legal system has its roots in British colonial legacy But in case of marriage or inherent property law Bangladesh follows the religious law of Islam The Quran or Hadith do not have a specific guideline concerning transgender and the Muslim countries do not follow any homogenous law due to the contextual cultural construction This paper argues without addressing the cultural practices of Islam the proper conceptualization of transgender identity is not possible Although it is also the case only the Islamic perspective will give us a narrow understanding of hijras who are one of the transgender communities in Bangladesh To do so this paper will analyze the dynamic relation between Islam and transgenderism in Bangladesh with a special reference to sharia law and explore the asymmetrical power relations to construct the reality of the Trans as well as the cultural perception of the hijra in Bangladesh